A simplified physically-based model for core dam overtopping breach. (August 2018) - Zhong, Qiming; Chen, Shengshui; Deng, Zhao
Abstract: Based on the breach mechanism of the core dam due to overtopping failure, a simplified physically-based model has been proposed in this study. A hydraulic method was used to predict the initial scour position for high dam. A time averaged erosion equation was adopted to simulate the backward erosion of dam's shoulder. The broad-crested weir equation was adopted to calculate the breach flow discharge. Furthermore, the sliding or overturning failure was adopted as the key mechanism for the core, which was judged based upon numerical analysis. The results showed that the model allowed for one-side and two-side erosions, as well as for the dam base erosion. An iterative method is developed to simulate the coupling process of soil and water at each time step. The failure of Banqiao dam was used as an illustrative example, as detailed data about its failure is available in literature. Nine core dam breach cases, caused by overtopping, were studied to verify the model. Meanwhile, three typical parametric breach models were chosen to compare the results with those obtained from the proposed model. The back analysis and comparison results demonstrated that the proposed physically-based model not only provided satisfactory results, but also performed better and produced more detailed results than the parametric model. Moreover, the calculated results indicated that the overturning failure was the dominating failure mode for the core failure. Highlights: We model the whole process of core dam breaching. Different failure modes of core are taken into account. The proposed model is testified by 10 core dam failure cases. The comparison shows that the proposed model can perform better than a parametric model.